Gut mycobiome dysbiosis contributes to the development of hypertension and its response to immunoglobulin light chains - Zou, Yeqing; Ge, Anxing; Lydia, Brako; Huang, Chen; Wang, Qianying; Yu, Yanbo (Frontiers in Immunology, 2022)
Abstract Objectives: Human gut microbiome has gained great attention for its proposed roles in the development of hypertension. The fungal microbiome in the human gut (i.e. the mycobiome) is beginning to gain recognition as a fundamental part of our microbiome. However, the existing knowledge of human mycobiome has never revealed the association between gut mycobiome and hypertension. It is known that inflammation and immunity contribute to human hypertension. Here, we sought to investigate whether gut mycobiome could predict the development of hypertension and its association with immunoglobulin light chains. Methods and materials: Participants were classified into three cohorts: prehypertension (pre-HTN), hypertension (HTN), and normal-tension (NT) based on their blood pressure. Fresh samples were collected, and the ITS transcribed spacer ribosomal RNA gene sequence was performed. An immunoturbidimetric test was used to examine the serum levels of immunological light chains. Results: Subjects in both of the states of pre-HTN and HTN had different fungal microbiome community compared to the NT group (FDR<0.05). Slightly higher levels of fungal richness and diversity were observed in the groups of pre-HTN and HTN. The relative abundance of Malassezia increased in the HTN group compared to that in the NT group, and the relative abundance of Mortierella enriched in the NT group. For the pre-HTN group, the relative abundance of Malassezia was positively associated with serum the concentration of light chain (LC) κ (r=0.510, P=0.044); for the HTN group, the relative abundance of Mortierella was positively associated with the serum concentration of LC κ (P<0.05), the relative abundance of Malassezia was positively associated with both the serum concentrations of LC κ and LC λ (r>0.30, P<0.05). Conclusions: Our present study demonstrated that gut fungal dysbiosis occurred in the state of prehypertension, and fungal dysbiosis can predict the dysregulation of serum light chains in hypertension patients. Further study on modulating gut fungal community should be focused on balancing the immunological features in hypertension.